Attention and basic literacy and numeracy in children with Autism Spectrum Disorder: A one-year follow-up study. (January 2015) - May, T.; Rinehart, N.J.; Wilding, J.; Cornish, K.
Highlights: We examined word reading and numerical operations in children with ASD. We investigated if attention constrained academic performances one year later. Academic performance in ASD was similar to typically developing children. Children with ASD made more attention switching errors. Attentional components correlated with word reading and numerical operations. Abstract: Little is known about the link between Executive Functioning (EF) and academic performance in children with Autism Spectrum Disorder (ASD) and how such links develop over time. This study examined word reading, basic mathematics, attention switching, sustained attention and their development. Two age, gender and perceptual IQ matched groups of cognitively able 7–12 year olds (ASD N  = 40; typical developing [TYP] N  = 40) were assessed at baseline and one year later, completing Word Reading and Numerical Operations tests and computerized tasks tapping attention switching and sustained attention. Children with ASD had similar word reading and numerical operations performance and similar development of these skills relative to TYP children. A delay in attention switching but similar development was found in children with ASD relative to TYP children. The EF tasks were correlated with reading and mathematics in ASD children only, however, in regression analyses these factors were not significant predictors of Time 2 reading and mathematics after accounting for Time 1 reading and mathematics scores. These findings indicate similar word reading and mathematics development but atypical attention profiles in cognitively able children with ASD. Implications for educators are discussed.